PFAS policies and reductions in drinking water contamination across the United States: Incorporated policy perspectives from Los Angeles residents - Shiwen Li; Rebecca Schielzeth; Tamar Galindo; Connie Valencia; Adam L. Smith; Lida Chatzi; Max T. Aung (Next Research, 2026)

Associations between per- and polyfluoroalkyl substances and metabolic dysfunction-associated steatotic liver disease in adolescents and young adults: modifying roles of age, lifestyle factors, and PNPLA3 genotype - Shiwen Li; Jiawen Carmen Chen; Elizabeth Costello; Douglas I. Walker; Jesse A. Goodrich; Lily Dara; Lucy Golden-Mason; Ana C. Maretti-Mira; Scott M. Bartell; Veronica M. Vieira; Tanya L. Alderete; Michael I. Goran; et al. (Environmental Research, 2026)

Psychosocial stressors as modifiers of the associations between well-studied and understudied chemicals and birth outcomes in the ECHO Cohort - Stephanie M. Eick; Patricia A. Brennan; Jessie P. Buckley; Donghai Liang; Xiuhong Li; Kayla L. Karvonen; Whitney Cowell; Yeyi Zhu; Emily S. Barrett; Alicia K. Peterson; Brennan H. Baker; Max Aung; et al. (Environmental Pollution, 2026)

Gestational PFAS concentrations in association with maternal depression and perceived stress during pregnancy and postpartum in the ECHO cohort - Susanna D. Mitro; Wei Yang; Assiamira Ferrara; Monique M. Hedderson; Max Aung; Himal Suthar; Radhika S. Raghunathan; Yeyi Zhu; Alicia K. Peterson; Morgan Reynolds; Kurunthachalam Kannan; Emily Oken; et al. (Environmental Research, 2025)

Mediating role of proteomics in the association between per- and polyfluoroalkyl substance exposure and blood pressure in youth - Jiawen Carmen Chen; Jesse A. Goodrich; Jiawen Liao; Shiwen Li; Qiran Jia; Douglas I. Walker; Elizabeth Costello; Tanya L. Alderete; Michael I. Goran; Damaskini Valvi; Shudi Pan; Brittney O. Baumert; et al. (Environmental Pollution, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

The potential mediating role of the gut microbiome and metabolites in the association between PFAS and kidney function in young adults: A proof-of-concept study - Hailey E. Hampson; Shiwen Li; Douglas I. Walker; Hongxu Wang; Qiran Jia; Sarah Rock; Elizabeth Costello; Petter Bjornstad; Laura Pyle; Jonathan Nelson; Frank D. Gilliland; Zhanghua Chen; et al. (Science of The Total Environment, 2024)

Organophosphate ester flame retardant chemicals and maternal depression during pregnancy - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Max T. Aung; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Tingyu Yang; Mario J. Vigil; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; et al. (Environmental Research, 2024)

Exposure to per- and polyfluoroalkyl substances and alterations in plasma microRNA profiles in children - Yijie Li; Brittney O. Baumert; Nikos Stratakis; Jesse A. Goodrich; Haotian Wu; Shelley H. Liu; Hongxu Wang; Emily Beglarian; Scott M. Bartell; Sandrah Proctor Eckel; Douglas Walker; Damaskini Valvi; et al. (Environmental Research, 2024)

Metabolic Perturbations Associated with both PFAS Exposure and Perinatal/Antenatal Depression in Pregnant Individuals: A Meet-in-the-Middle Scoping Review - Himal Suthar; Roselyn B. Tanghal; Lida Chatzi; Jesse A. Goodrich; Rachel Morello-Frosch; Max Aung (Current Environmental Health Reports, 2024)
Purpose of Review Depression during the perinatal or antenatal period affects at least 1 in 10 women worldwide, with long term health implications for the mother and child. Concurrently, there is increasing evidence associating maternal exposure to per- and poly-fluoroalkyl substances (PFAS) to adverse pregnancy outcomes. We reviewed the body of evidence examining both the associations between PFAS exposure and perturbations in the maternal metabolome, and the associations between the maternal metabolome and perinatal/antenatal depression. Through this, we sought to explore existing evidence of the perinatal metabolome as a potential mediation pathway linking PFAS exposure and perinatal/antenatal depression. Recent Findings There are few studies examining the metabolomics of PFAS exposure—specifically in pregnant women—and the metabolomics of perinatal/antenatal depression, let alone studies examining both simultaneously. Of the studies reviewed ( N = 11), the majority were cross sectional, based outside of the US, and conducted on largely homogenous populations. Our review identified 23 metabolic pathways in the perinatal metabolome common to both PFAS exposure and perinatal/antenatal depression. Summary Future studies may consider findings from our review to conduct literature-derived hypothesis testing focusing on fatty acid metabolism, alanine metabolism, glutamate metabolism, and tyrosine metabolism when exploring the biochemical mechanisms conferring the risk of perinatal/antenatal depression due to PFAS exposure. We recommend that researchers also utilize heterogenous populations, longitudinal study designs, and mediation approaches to elucidate key pathways linking PFAS exposures to perinatal/antenatal depression.

Exposure to perfluoroalkyl substances and longitudinal changes in bone mineral density in adolescents and young adults: A multi-cohort study - Emily Beglarian; Elizabeth Costello; Douglas I. Walker; Hongxu Wang; Tanya L. Alderete; Zhanghua Chen; Damaskini Valvi; Brittney O. Baumert; Sarah Rock; Bruna Rubbo; Max T. Aung; Frank D. Gilliland; et al. (Environmental Research, 2024)

Per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers and dysregulation of MicroRNA expression in humans and animals—A systematic review - Yijie Li; Brittney O. Baumert; Elizabeth Costello; Jiawen Carmen Chen; Sarah Rock; Nikos Stratakis; Jesse A. Goodrich; Yinqi Zhao; Sandrah P. Eckel; Douglas I. Walker; Damaskini Valvi; Michele A. La Merrill; et al. (Environmental Research, 2024)

Prenatal exposures to organophosphate ester metabolites and early motor development in the MADRES cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Xinci Chen; Tingyu Yang; Mario J. Vigil; Helen B. Foley; Kurunthachalam Kannan; Morgan Robinson; Brendan Grubbs; Deborah Lerner; Nathana Lurvey; Laila Al-Marayati; et al. (Environmental Pollution, 2024)

Associations of per- and polyfluoroalkyl substances, polychlorinated biphenyls, organochlorine pesticides, and polybrominated diphenyl ethers with oxidative stress markers: A systematic review and meta-analysis - Jiawen Carmen Chen; Brittney O. Baumert; Yijie Li; Yiping Li; Shudi Pan; Shante Robinson; Bruna Rubbo; Elizabeth Costello; Jie He; Hailey Hampson; Emily Beglarian; Sarah Rock; et al. (Environmental Research, 2023)

Sex-specific effects of prenatal organophosphate ester (OPE) metabolite mixtures and adverse infant birth outcomes in the maternal and developmental risks from environmental and social stressors (MADRES) pregnancy cohort - Ixel Hernandez-Castro; Sandrah P. Eckel; Caitlin G. Howe; Zhongzheng Niu; Kurunthachalam Kannan; Morgan Robinson; Helen B. Foley; Brendan Grubbs; Laila Al-Marayati; Deborah Lerner; Nathana Lurvey; Max T. Aung; et al. (Environmental Research, 2023)

Metals Exposures and DNA Methylation: Current Evidence and Future Directions - Elana R. Elkin; Cesar Higgins; Max T. Aung; Kelly M. Bakulski (Current Environmental Health Reports, 2022)